Diabetes in Ontario: Determination of prevalence and incidence using a validated administrative data algorithm - HUX, Janet E; IVIS, Frank; FLINTOFT, Virginia; BICA, Adina (Diabetes care, 2002)
Accurate information about the magnitude and distribution of diabetes can inform policy and support health care evaluation. We linked physician service claims (PSCs) and hospital discharge abstracts (HDAs) to determine diabetes prevalence and incidence. A retrospective cohort was constructed using administrative data from the national HDA database, PSCs for Ontario (population 11 million), and registries carrying demographics and vital statistics. All HDAs and PSCs bearing a diagnosis of diabetes (ICD9-CM 250) were selected for 1991-1999. Two previously reported algorithms for identification of diabetes were applied as follows: "1-claim" (any HDA or PSC showing diabetes) and "2-claim" (one HDA or two PSCs within 2 years showing diabetes). Incident cases were defined as individuals who met the criteria for diabetes for the first time after at least 2 years of observation. For validation, diagnostic data abstracted from primary care charts (n=3,317) of 57 randomly selected physicians were linked to the administrative data cohort, and sensitivity and specificity were calculated. -In 1998, 696,938 individuals met the 1-claim criteria and 528,280 met the 2-claim criteria. Sensitivity for diabetes was 90 and 86%; for the 1- and 2-claim algorithms, specificity was 92 and 97%, respectively, and positive predictive values were 61 and 80%, respectively. Using the 2-claim algorithm, the all-age prevalence increased from 3.2% in 1993 to 4.5% in 1998 (6.1% in adults). Incidence remained stable. Administrative data can be used to establish population-based incidence and prevalence of diabetes. Diabetes prevalence is increasing in Ontario and is considerably higher than self-reported rates.